Kill The Messenger - Cuesta, Michael, 1963-; Renner, Jeremy; Patrick, Robert, 1958-; Sims, Jena; Johnson, Nathan, 1976- (Universal City, CA : Universal Studios Home Entertainment, 2015)
Based on a true story, journalist Gary Webb investigates a story that exposes the CIA's ties to drug dealers smuggling cocaine into the U.S. and profits from drug sales going to arm Contra rebels in Nicaragua.
Originally released as a motion picture in 2014.
Based on the books "Dark alliance" by Gary Webb and "Kill the messenger" by Nick Schou.
Dolby digital 5.1, anamorphic wide screen 2.40:1.
Features: deleted scenes, Kill the messenger : the all-star cast, Crack in America, Filming in Georgia, director commentary.
Cinematography, Sean Bobbitt ; production design, John Paino ; editor, Brian A. Kates ; music, Nathan Johnson.
Jeremy Renner, Robert Patrick, Jena Sims, Robert Pralgo, Hajji Golightly.
Keywords: Webb, Gary, -- 1955-2004 -- Drama; Webb, Gary, -- 1955-2004 -- Film adaptations; Schou, Nick -- Film adaptations; United States. -- Central Intelligence Agency -- Drama; Counterrevolutionaries -- Nicaragua -- Drama; Cocaine -- United States -- Drama; Drug traffic -- United States -- Drama; Fiction films; Video recordings for the hearing impaired; Thriller films; Based on the book; Feature films; Biographical films